A framework of meaningful sharing behavior of authentic holy Quran content on facebook / Suraya Ika Tamrin - Suraya Ika , Tamrin (2021)
Apparently, people have witnessed a rapid diffusion and adoption of social media platforms in finding and sharing information, including the religious contents of Quran. This exercise has led to unhealthy sharing behavior of online Quran content among the users and the increase number of disseminations of unauthenticated online Quran content. There are several previous researches have been conducted in the context or religious content sharing in social media. However, there are limited works done to address both mentioned issues above. Thus, it is vital to continuously monitor this Quran content disseminated in the social media are authentic and not changed. This research embarks on four main objectives, 1) to investigate the current behavior of Facebook users in sharing Quran content; 2) to develop a framework to authenticate the online Quran content shared on Facebook; 3) to evaluate the factors that associated with Quran content sharing on Facebook, and 4) to validate a framework to authenticate the online Quran content shared on Facebook. To achieve these objectives, this research applied sequential mixed method, which are i) qualitative netnography analysis and ii) quantitative survey questionnaire. The qualitative netnography focused on 92 Quran related groups in Facebook for the duration of 12 months in two different data collection series. For the quantitative data collection, it involved 587 respondents based on convenient sampling method in Facebook. The finding shows there are 12 validated constructs: Verification, legality, trustworthy, privacy, self-efficacy, response efficacy, response cost, perceived severity, perceived vulnerability, fear, authentication motivation and healthy sharing behavior. Whereby, each construct shows significant relationship at p >0.05. The conclusion of the research shows that 26 hypotheses are supported with R2 of the healthy sharing behavior is at 66.2% and 5 hypotheses are not supported. The contribution of this research is in 2 folds which are, 1) in the body of knowledge – 12 additional constructs are required to show healthy sharing behavior; 2) as for the stakeholders, Facebook users, Muslim community, and Malaysia Islamic authority, would be able to use this framework as a guidance in executing healthy behavior in sharing Quran content.